Potent Lipophilic Melatoninergic x-fluoro-y-methoxy Substituted Phenylalkylamides: Molecular Dynamics Calculations and in vitro Modified Release in Aqueous Media from Tablet Formulations - Vlachou, Marilena; Siamidi, Angeliki; Anagnostopoulou, Dionysia; Protopapa, Chrystalla; Kompogennitaki, Rodoula; Sakellaropoulou, Aikaterini; Efstathiou, Natasa; Papanastasiou, Ioannis; Billia, Maria; Mavromoustakos, Thomas (Current Pharmaceutical Design, 2023)
Introduction: We report herein on the design and development of matrix tablets containing potent synthetic melatonin (MLT) receptor analogues, the x-fluoro-y-methoxy substitiuted phenylalkylamides (compounds I-IV), the preparation and melatoninergic potency of which was recently communicated. Methods: The presence of the fluorine atom in compounds I-IV, besides not affecting their binding affinity, compared to the pineal hormone melatonin, it also slows down their metabolism, which is a major drawback of MLT. However, as fluorine increases the lipophilicity, solid pharmaceutical formulations of I-IV, involving the appropriate biopolymers for their modified release in aqueous media, were developed in the context of the present work. Results: The release profile of analogues I-IV was found to be similar to that of MLT and also of the commercially available drug, Circadin®. Some of these systems are suitable for dealing with sleep onset problems, whilst others for dealing with combined sleep onset/sleep maintenance problems. Conclusion: Apart from the nature and relevant content of the formulants used, this bimodal release profile of the new analogues depends, to a large extent, on the diverse structural arrangement of their side chains in space, as nicely demonstrated by the molecular dynamics calculations, conducted in the context of this study.
Keywords: dissolution